Efek Anti-hiperkolesterolemik Ekstrak Etanol Daun Cnidosculus aconitifolius terhadap Pembentukan Lesi Aterosklerosis Arteri Koroner pada Tikus Wistar Jantan yang Diberi Diet Aterogenik (Rattus norvegicus): Hasil Penelitian - Ni Ketut Rake Putri Saraswati; Ida Sri Iswari; I Wayan Juli Sumadi (PT Kalbe Farma Tbk., 2025)
Introduction: Foods high in cholesterol increase the production of free radicals and inflammation, and may also trigger the formation of atherosclerotic lesions. Cnidosculus aconitifolius or tree spinach leaves were known to have antioxidant and anti-inflammatory activities. This study was to determine the effect of Cnidosculus aconitifolius on blood cholesterol level and coronary artery atherosclerotic lesions formation using a rat model. Methods: A randomized post-test-only control group of 30 male Wistar rats (Rattus norvegicus), aged 2-3 months, randomly divided into 3 groups: standard control was given regular food; negative control was given an atherogenic diet; and the treatment group was given an atherogenic diet + Cnidosculus aconitifolius leaf ethanol extracts. The treatment lasted 44 days. Data was analyzed with OneWay ANOVA and Kruskal-Wallis test. Results: The total cholesterol and LDL levels were significantly lower in the treatment group compared to the control group (p<0.001). A decrease of atherosclerotic lesion scores in the treatment group compared to the control (p=0.010) was also observed. Conclusion: Cnidosculus aconitifolius leaf ethanol extracts have an anti-hypercholesterolemic effect, hence the potential to prevent the formation of atherosclerotic lesions in the coronary arteries of hypercholesterolemic Wistar rats.